Editorial - Mensah Danquah, Monica (Ghana Library Journal, 2022)
This issue of the Ghana Library Journal contains twelve articles and a Festschrift. Articles in this issue are primarily the remaining papers resulting from the call for papers by the Journal in February 2022. Readers may notice that the Vol 27 no. 1 and this current issue introduce the use of ‘Digital Object Identifiers’ (DOIs) in the Ghana Library Journal for the first time, where DOIs are assigned to each manuscript published in the Journal. This means a reassurance that references cited can be located even if URLs of the websites to which these documents are affiliated change. As a larger project, the editorial team of the Ghana Library Journal is working tirelessly to assign DOIs to manuscripts in all back issues of the GLJ, getting indexed as a DOAJ, as well as getting indexed in Google Scholar and Scopus. I encourage you to submit your manuscript to the GLJ, as this Journal is poised to become one of the most effective vehicles for the dissemination of academic and research information in the library and information science profession. I want to once again thank all members of the Editorial team as well as the reviewers for their enormous support in making this issue of the journal a success.